Gastroschisis: Impact of Bedside Closure on Ventilator-Associated Outcomes - Campbell, Alison Morag; Motawea, Mahmoud; Fradley, Wayne; Marven, Sean (European Journal of Pediatric Surgery, 2022)
Aim In our practice, preformed silos are routine rather than reserved for difficult cases. We aimed to identify whether silo and bedside closure can minimize: general anesthetic (GA) exposure, need for intubation and ventilation, or days intubated for neonates with simple gastroschisis (SG).Methods After approval, patients were identified via the neonatal discharge log (April 2010 to April 2019). Data were collected by case-note review and analyzed with respect to GA, ventilation, and core outcomes.Results Of 104 patients (50 female, mean birth weight 2.43 kg, mean gestational age 36 + 2 weeks), 85 were SG and 19 complex. Silo application was initial management in 70 SG, 57 completed successful bedside closure (by day 4 of life—median). Fifteen SG had initial operative closure.Of the 70 SG managed with silo, 46 (66%) had no GA as neonates. Twelve required GA for line insertion. Thirteen patients with initial silo had closure in theater (7 opportunistic at time of GA for line). Nine required intubation and ventilation out-with the operating theater during neonatal management. Seven had already been intubated at delivery; 3 because of meconium aspiration.One-hundred percent of those treated with operative closure had GA, 1 patient subsequently required surgery for subglottic stenosis. Time to full feeds did not differ between groups.Conclusion Silo and bedside closure allow the majority of SG neonates to avoid GA or intubation in the neonatal period, without increased risk of complication. However, it is important that the nursing expertise required to manage these patients safely is not underestimated.
Keywords: gastroschisis; core outcomes; ventilation